Cache-Enabled MIMO Power Line Communications With Precoding Design in Smart Grid; IEEE Transactions on Green Communications and Networking; Vol. 4, iss. 1 - Qian Yuwen; Shi Liuqiang; Long Shi; Li Jun; Shu Feng; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Yuan Jinhong (2020, 2020)
Title screen